2019
DOI: 10.1002/cncr.32643
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of returning to work and its impact on survival in survivors with oral cancer: A 5‐year follow‐up study

Abstract: Background A return to work (RTW) is a challenge for survivors of oral cancer. Further light could be shed on the RTW of patients with oral cancer, which remains largely uninvestigated. The objective of this study was to investigate the trajectories of RTW and their impact on survival in workers with oral cancer. Methods In total, 12,222 workers who were newly diagnosed with oral cancer were identified during the period from 2004 to 2015 and were included in this cohort study. The associations between independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
(112 reference statements)
1
11
0
2
Order By: Relevance
“…However, according to the analysis of the national health insurance data, about half of all working cancer patients lose their jobs after receiving a cancer diagnosis, and only up to 40% of them are reemployed [8,9]. This may be attributed to various reasons, but the key influencing factors seem to be: gender, age, occupation type, level of income [9], medical conditions including chemotherapy [10], and comorbidities [11]. Furthermore, the level of understanding from co-workers, social support system available to the patient, information sharing [12], the prevailing stigma, and the presence/absence of discrimination toward cancer patients [13] have also been suggested to affect patients' work-related decisions.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the analysis of the national health insurance data, about half of all working cancer patients lose their jobs after receiving a cancer diagnosis, and only up to 40% of them are reemployed [8,9]. This may be attributed to various reasons, but the key influencing factors seem to be: gender, age, occupation type, level of income [9], medical conditions including chemotherapy [10], and comorbidities [11]. Furthermore, the level of understanding from co-workers, social support system available to the patient, information sharing [12], the prevailing stigma, and the presence/absence of discrimination toward cancer patients [13] have also been suggested to affect patients' work-related decisions.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the risk factors affecting returning to work of cancer survivors included personal, employment, and socioeconomic factors 15 . Chen et al demonstrated that RTW may have a beneficial effect on the survival of patients with oral cancer in Taiwan 16 . Among the cancer and symptom factors , in our study, the chances of returning to work were higher for the patients who received surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The survival and recurrence differences in both ALaCaRT and other trials have shown no significant difference between open and laparoscopic approaches 20 . Given that maintaining employment is an important patient‐centered outcome for cancer survivors, their family members and society, 31‐33 the potential impact of laparoscopic‐assisted surgery on RTW could be promoted to new patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our research identified several factors that were associated with RTW, including being employed in a full‐time rather than part‐time capacity presurgery, and not having distant metastases at time of surgery. As a minimally invasive surgery, faster RTW, which contributes to income, a sense of structure and social recovery, 31‐33 has been one of the main objectives of undergoing laparoscopic‐assisted surgery for abdominal and pelvic procedures. Type of surgery, age, sex, and surgical outcome (successful versus unsuccessful), were not significant predictors of RTW for rectal cancer patients in most scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation